How can luxury brands maintain exclusivity by promoting a digital channel as the main touchpoint with the customer? The Josefinas and Manjerica cases - Torgal, Joana Miguel Vidreiro de Morais Sarmento (2022)
For years, several luxury brands were reluctant to operate through digital channels, as they believed it promoted a democratisation of luxury. Currently, the industry faces several challenges due to the entry into it and the paradox of rarity that puts in question the main pillars of luxury - rarity and exclusivity. This dissertation has as main objective to understand how brands that prioritize digital encounters, manage to retain customers through these same channels, what are the strategies chosen to create a luxurious experience with the absence of frontline staff and understand if these overcome the paradox that the industry faces. To have more information on the subject, two semi-structured interviews were conducted with two Portuguese luxury brands that operate only in digital, to understand what their perception about their customers is, what are the strategies chosen to maintain a strong contact with them so that they do not miss a physical shop and at what moments there is a personalization and a co-creation with the customer. To conclude, digital luxury consumers look for brands that can bridge the gap between online and offline, where there are moments of co-creation and attention with them.